THE EFFECTIVENESS OF COMICS LEARNING MEDIA TO IMPROVE THE TOLERANCE ATTITUDE OF JUNIOR HIGH SCHOOL LEVEL STUDENTS - Anggraeni Sugiarto, Apprillia; Kurniawan , Dandi; Ridwan, Muhammad; Sudarwati, Ninik (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
The motto